Bioeconomics and sustainability : essays in honor of Nicholas Georgescu-Roegen - Georgescu-Roegen, Nicholas; Mayumi, Kozo; Gowdy, John M. (Cheltenham, UK ; Northampton, MA, USA : E. Elgar, 1999)
This important book addresses the prospect for reconciling economic competiveness with sustainable development. it shows that we cannot simply assume that changes in public attitudes, business policies and government regulation will guarantee the conditions for long term ecological, social and economical sustainability.
Includes bibliographical references and index.
nmn, 08/08/16
Loan
Keywords: Environmental economics; Sustainable development; Economics; Human ecology; Entropy